STUDENTS PERCEPTION ABOUT ZOOM MEETING APPLICATION INTEGRATION IN (EFL) CLASROOM - Oktasari, Vivin Diah; Al Fauzi, Fatih (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
This study aims to determine students' perceptions of learning English class (EFL) in the language material evaluation course and the development of Zoom meeting application integration. This study was qualitative descriptive. Because to understand and interpret student perceptions on the experience of using the Zoom application in EFL classes. The Analysis of interviews and questionaires by means of data reduction, data display, and drawing conclusions from research problems. The Results, of interviews with 8 questions and a questionnaire consisting of 20 questions items for students, there are some difficulties that students may face when learning in EFL classes using the Zoom application. One of the most significant difficulties faced by students in using the Zoom application in language learning is a weak signal and quota. Because students will miss the material delivered by the lecturer and spend quotas a lot different from other applications.